Effect of growth parameters on the properties of RF-sputtered highly conductive and transparent p-type NiOx films. (5th April 2016) - Grilli, M L; Menchini, F; Dikonimos, T; Nunziante, P; Pilloni, L; Yilmaz, M; Piegari, A; Mittiga, A
Abstract: Highly conductive and transparent NiOx films can be very useful as buffer layers for the optimization of the p-type contacts of optoelectronic devices. Thin NiOx films were fabricated by reactive radio frequency (RF) sputtering at room temperature starting from a Ni target. A systematic study of the influence of oxygen partial pressure, RF power and sputtering gas pressure on the films' properties was carried out. The structural, microstructural, optical and electrical properties were affected differently by the sputtering parameters. Resistivity decreased by increasing the oxygen partial pressure and the sputtering total pressure and by decreasing the RF power, while transmittance increased by decreasing the oxygen partial pressure and by increasing the RF power and sputtering pressure. Minimum resistivity of 1.6 × 10 −2 Ωcm and a visible transmittance of 40% were achieved for a film grown in a pure oxygen atmosphere, while a higher transmittance of 54% and a resistivity of ρ = 1.1 × 10 −1 Ωcm were obtained for a film grown at 30% oxygen partial pressure. The trends of transmittance and resistivity as a function of the oxygen pressure during the sputtering process can be explained in terms of the amount of Ni 3+ defects deduced by x-ray photoelectron spectroscopy (XPS) measurements. The full interpretation of the other results is less straightforward and highlights the relevance of the samples' structural properties.